Long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency with inadvertent caries in infants - FELIX BLAKE, MARCO BLESSMANN, HEINER WERLE, LEI LI & ALI GBARA (IAPD and Blackwell, 2007)
Long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency (LCHADD) is a rare systemic disease that is associated with early tooth decay.